# Class 10 RD Sharma Solutions – Chapter 9 Arithmetic Progressions – Exercise 9.3

• Difficulty Level : Medium
• Last Updated : 21 Jul, 2021

### (i) -5, -1, 3, 7, …………

Solution:

Given sequence is -5, -1, 3, 7, …………

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12.

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.

∴ First term is -5

And, common difference = a2 – a1 = -1 – (-5) = 4

∴ Common difference is 4

### (ii) 1/5, 3/5, 5/5, 7/5, ……

Solution:

Given sequence is 1/5, 3/5, 5/5, 7/5, ……

∴ First term is 1/5

And, common difference = a2 – a1 = 3/5 – (1/5) = 2/5

∴ Common difference is 2/5

### (iii) 0.3, 0.55, 0.80, 1.05, …………

Solution:

Given sequence is 0.3, 0.55, 0.80, 1.05, …………

∴ First term is 0.3

And, common difference = a2 – a1 = 0.55 – (0.3) = 0.25

∴ Common difference is 0.25

### (iv) -1.1, -3.1, -5.1, -7.1, …………..

Solution :

Given sequence is -1.1, -3.1, -5.1, -7.1, …………..

∴ First term is -1.1

And, common difference = a2 – a1 = -3.1 – (-1.1) = -2.0

∴ Common difference is -2.0

### (i) a = 4, d = -3

Solution:

Given:

a1 = 4 and d= -3

Therefore, arithmetic progression is: a, a + d, a + 2d, a + 3d, ……

⇒ 4, 4 – 3, 4 + 2(-3), 4 + 3(-3), ……

⇒ 4, 1, – 2, – 5, – 8 ……..

∴ A.P will be 4, 1, – 2, – 5, – 8 ……..

### (ii) a = -1, d = 1/2

Solution:

Given:

a1 = -1, d= 1/2

Therefore, arithmetic progression is: a, a + d, a + 2d, a + 3d, ……

⇒ -1, -1 + 1/2, -1, 2½, -1 + 3½, …

⇒ -1, -1/2, 0, 1/2

∴ A.P will be -1, -1/2, 0, 1/2

### (iii) a = -1.5, d = -0.5

Solution:

Given:

a1 = -1.5, d = -0.5

Therefore, arithmetic progression is: a, a + d, a + 2d, a + 3d, ……

⇒ -1.5, -1.5, -0.5, –1.5 + 2(– 0.5), –1.5 + 3(– 0.5)

⇒ – 1.5, – 2, – 2.5, – 3, …….

∴ A.P will be – 1.5, – 2, – 2.5, – 3, …….

### (i) The cost of digging a well for the first meter is ₹ 150 and rises by ₹ 20 for each succeeding meter.

Solution:

Given:

Cost of digging a well for the first meter = ₹150

Therefore,

Cost for the second meter = ₹150 + ₹20 = ₹170

Cost for the third meter = ₹170 + ₹20 = ₹190

Cost for the fourth meter = ₹190 + ₹20 = ₹210

Since, 20 is added fo each succeeding meter

Hence, the sequence will be (In rupees) and is A.P

150, 170, 190, 210, ………..

∴ The given sequence is in A.P and common difference is 20

### (ii) The amount of air present in the cylinder when a vacuum pump removes each time 1/4 of the remaining in the cylinder.

Solution:

Air removed for the first time = (1 x 1/4) = 1/4

Remaining air = 1 – 1/4 = 3/4

Air removed for the second time = (3/4 x 1/4) = 3/16

Remaining air = 3/4 – 3/16 = 9/16

Air removed for the third time = (9/16 x 1/4) = 9/64

Remaining air = 9/16 – 9/64 = 27/64

∴The sequence will be 1, 3/4, 9/16, 27/64

Here, a2 – a1 = 3/4 – (1) = -1/4

a3 – a2 = 9/16 – (3/4) = -3/16

Since, the successive difference of list is not same

∴ The given sequence is not in A.P

### (iii) Divya deposited Rs 1000 at compound interest at the rate of 10% per annum. The amount at the end of first year, second year, third year, …, and so on.

Solution:

Given:

Divya deposited Rs 1000 at compound interest of 10% p.a

So, the amount at the end of first year is = 1000 + 0.1(1000) = Rs 1100

And, the amount at the end of second year is = 1100 + 0.1(1100) = Rs 1210

And, the amount at the end of third year is = 1210 + 0.1(1210) = Rs 1331

Here, a2 – a1 = 1210 – 1100 = 110

a3 – a2 = 1331 – 1210 = 121

Since, the successive difference of list is not same

∴ The given sequence is not in A.P

### (i) 1, -2, -5, -8, ……..

Solution:

Given:

First term = 1, Second term = -2

Common difference = -2 – (1) = -3

Now,

Fifth term = -8 + (-3) = -11

Sixth term = -11 + (-3) = -14

Seventh term = -14 + (-3) = -17

Eighth term = -17 + (-3) = -20

### (ii) 0, -3, -6, -9, ……

Solution:

Given:

First term = 0, Second term = -3

Common difference = -3 – (0) = -3

Now,

Fifth term = -9 + (-3) = -12

Sixth term = -12 + (-3) = -15

Seventh term = -15 + (-3) = -18

Eighth term = -18 + (-3) = -21

### (iii) -1, 1/4, 3/2, ……..

Solution:

Given:

First term = -1, Second term = 1/4

Common difference = 1/4 – (-1) = 5/4

Now,

Fifth term = 3/2 + (5/4) = 11/4

Sixth term = 11/4 + (5/4) = 4

Seventh term = 4 + (5/4) = 21/4

Eighth term = 21/4 + (5/4) = 26/4

### (iv) -1, – 5/6, – 2/3, ………..

Solution:

Given:

First term = -1, Second term = -5/6

Common difference = -5/6 – (-1) = 1/6

Now,

Fifth term = -2/3 + (1/6) = -1/2

Sixth term = -1/2 + (1/6) = -1/3

Seventh term = -1/3 + (1/6) = -1/6

Eighth term = -1/6 + (1/6) = 0

### Problem 5: Prove that no matter what the real numbers a and b are, the sequence with nth term a + nb is always an A.P. What is the common difference?

Solution:

an = a + nb

Let n= 1, 2, 3, 4, 5, ……….

a1 = a + b

a2 = a + 2b

a3 = a + 3b

a4 = a + 4b

a5 = a + 5b

Now,

a2 – a1 = (a + 2b) – (a + b) = b

a3 – a2 = (a + 3b ) – (a + 2b) = b

a4 – a1 = (a + 4b) – (a + 3b) = b

a5 – a4 = (a + 5b) – (a + 4b) = b

Hence, proved

### (i) 3, 6, 12, 24, ………………………………

Solution:

Now,

a2  – a1 = 6 – (3) = 3

a3 – a1 = 12 – (6) = 6

a4 – a1 = 24 – (12) = 12

Since, the successive difference of list is not same

∴ The given sequence is  not in A.P

### (ii) 0, -4, -8, -12, ……………………………………………………

Solution:

Now,

a2  – a1 = -4 – (0) = -4

a3 – a2 = -8 – (-4) = -4

a4 – a3 = -12 – (-8) = -4

Since, the successive difference of list is same

∴ The given sequence is in A.P and common difference is -4

### (iii) 1/2, 1/4, 1/6, 1/8

Solution:

Now,

a2  – a1 = 1/4 – (1/2) = -1/4

a3 – a2 = 1/6 – (1/4) = -1/12

a4 – a3 = 1/8 – (1/6) = -1/24

Since, the successive difference of list is not same

∴ The given sequence is not in A.P

### (iv) 12, 2, -8, -18, ……………………………..

Solution:

Now,

a2  – a1 = 2 – (12) = -10

a3 – a2 = -8 – (2) = -10

a4 – a3 = -18 – (-8) = -10

Since, the successive difference of list is same

∴ The given sequence is in A.P

### (v) 3, 3, 3, 3, ………………………………………

Solution:

Now,

a2  – a1 = 3 – (3) = 0

a3 – a2 = 3 – (3) = 0

a4 – a3 = 3 – (3) = 0

Since, the successive difference of list is same

∴ The given sequence is in A.P and common difference is 0

### (vi) p, p + 90, p + 180, ………………..

Solution:

Now,

a2  – a1 = p+90 – (p) = 90

a3 – a2 = p+180 – (p+90) = 90

Since, the successive difference of list is same

∴ The given sequence is in A.P and common difference is 90

### (vii) 1.0, 1.7, 2.4, ………………………….

Solution:

Now,

a2  – a1 = 1.7 – (1.0) = 0.7

a3 – a2 = 2.4 – (1.7) = 0.7

Since, the successive difference of list is same

∴ The given sequence is in A.P and common difference is 0.7

### (viii) -225, -425, -625, …………………………….

Solution:

Now,

a2  – a1 = -425 – (-225) = -200

a3 – a2 = -625 – (-425) = -200

Since, the successive difference of list is same

∴ The given sequence is in A.P and common difference is -200

### (ix) 10, 10+25, 10+26, 10+27, …………………………………………..

Solution:

Now,

a2  – a1 = 10+25 – (10) = 32

a3 – a2 = 10+26 – (10+25) = 32

a4 – a3 = 10+27 – (10+26) = 64

Since, the successive difference of list is not same

∴ The given sequence is in A.P

### (x) a+b, (a+1)+b, (a+1)+(b+1), (a+2)+(b+1), ……………………………….

Solution:

Now,

a2  – a1 = ((a+1) + b) – (a + b) = 1

a3 – a2 = ((a+1)+(b+1)) – ((a+1)+b) = 1

a4 – a3 = ((a+2)+(b+1)) – ((a+1)+(b+1)) = 1

Since, the successive difference of list is same

∴ The given sequence is in A.P and common difference is 1

### (xi) 12, 32, 52, 72, ………………………………………………………

Solution:

Now,

a2  – a1 = (32 – 12) = 8

a3 – a2 = (52 – 32) = 16

a4 – a3 = (72 – 52) = 24

Since, the successive difference of list is not same

∴ The given sequence is not in A.P

### (xii) 12, 52, 72, 73, …………………………………………………………..

Solution:

Now,

a2  – a1 = 52 – 12 = 24

a3 – a2 = 72 – 52 = 24

a4 – a3 = 73 – 72 = 24

Since, the successive difference of list is same

∴ The given sequence is in A.P and common difference is 24

### (i) 51, 59, 67, 75, …….

Solution:

Given:

First term = 51, Second term = 59

Common difference = 59 – 51 = 8

Now,

Fifth term = 75 + 8 = 83

Sixth term = 83 + 8 = 91

### (ii) 75, 67, 59, 51, ………

Solution:

Given:

First term = 75, Second term = 67

Common difference = 67 – 75 = -8

Now,

Fifth term = 51 – 8 = 43

Sixth term = 43 – 8 = 35

### (iii) 1.8, 2.0, 2.2, 2.4, …….

Solution:

Given:

First term = 1.8, Second term = 2.0

Common difference = 2.0 – 1.8 = 0.2

Now,

Fifth term = 2.4 + (0.2) = 2.6

Sixth term = 2.6 + (0.2) = 2.8

### (iv) 0, 1/4, 1/2, 3/4, ………..

Solution:

Given:

First term = 0, Second term = 1/4

Common difference = 1/4 – 0 = 1/4

Now,

Fifth term = 3/4 + (1/4) = 1

Sixth term = 1 + (1/4) = 5/4

### (v) 119, 136, 153, 170, ………..

Solution:

Given:

First term = 119, Second term = 136

Common difference = 136 – 119 = 17

Now,

Fifth term = 170 + (17) = 187

Sixth term = 187 + (17) = 204

My Personal Notes arrow_drop_up